Enterprise application development with C# 10 and .NET 6 : become a professional .NET developer by learning expert techniques for building scalable applications - Akella, Ravindra; Tamirisa, Arun Kumar; Kunani, Suneel Kumar; Muthiyalu, Bhupesh Guptha (Packt Publishing Ltd., 2022)
A comprehensive guide to every important component of C# and .NET 6 required to build robust enterprise web applications. Building production-ready enterprise applications can be a challenging task due to the overabundance of tools and their different versions that make app development complex. This book simplifies the process with an end-to-end road map for building enterprise applications from scratch using the latest features of .NET Core 6 and C# 10. Throughout the book, you'll work on creating an enterprise app, adding a key component to the app with each chapter, before ﬁnally getting it ready for testing and deployment. You'll learn concepts relating to advanced data structures, the Entity Framework Core, parallel programming, and dependency injection. As you progress, you'll cover various authentication and authorization schemes provided by .NET Core to make your apps and APIs secure. The book then shows you how the latest Microsoft Visual Studio and C# 10 help you simplify developer tasks and shares tips and tricks in Visual Studio to improve your productivity. You'll discover various testing techniques, such as unit testing and performance testing, as well as diﬀerent methods to deploy enterprise apps. By the end of this book, you'll be able to create enterprise apps using the powerful features of .NET 6 and deploy them to the cloud while working with various cloud components using Azure.